2020
DOI: 10.3389/fnagi.2020.00190
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis Was Associated With a Faster Decline in Hippocampal Volumes in Cognitively Normal Older People

Abstract: Objective: To examine whether osteoarthritis (OA) is associated with a change in adjusted hippocampal volumes (HpVR: hippocampal/intracranial volume × 10 3) over time among cognitively normal older people. Methods: We examined the cross-sectional and longitudinal associations of OA with HpVR among individuals with normal cognition (NC) from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study. At baseline, a total of 372 individuals with NC were included. Results: In the cross-sectional analyses of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For more than a decade, ADNI researchers have been working to better understand AD. In addition to studying AD itself, many researchers, including ourselves, are interested in investigating the links between AD and other diseases, such as osteoarthritis (Li et al, 2020), Parkinson's disease (Wang et al, 2018), hearing loss (Xu et al, 2019), hypertension (Scott et al, 2015;Zhou et al, 2020), and hypercholesterolemia (Varma et al, 2021), from the ADNI database. To the best of our knowledge, this is the first study to demonstrate the links between OP and higher levels of CSF t-tau and p-tau 181 at baseline, and the faster volumetric declines of enterhinal cortex and hippocampus over time among older people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For more than a decade, ADNI researchers have been working to better understand AD. In addition to studying AD itself, many researchers, including ourselves, are interested in investigating the links between AD and other diseases, such as osteoarthritis (Li et al, 2020), Parkinson's disease (Wang et al, 2018), hearing loss (Xu et al, 2019), hypertension (Scott et al, 2015;Zhou et al, 2020), and hypercholesterolemia (Varma et al, 2021), from the ADNI database. To the best of our knowledge, this is the first study to demonstrate the links between OP and higher levels of CSF t-tau and p-tau 181 at baseline, and the faster volumetric declines of enterhinal cortex and hippocampus over time among older people.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to some wrong classifications. Even so, this is a common limitation of database-based research (Norton et al, 2014;Frain et al, 2017;Xu et al, 2019;Harshfield et al, 2020;Li et al, 2020;Kwon et al, 2021). Future studies are encouraged to extend our work to other databases to verify our results.…”
Section: Discussionmentioning
confidence: 99%
“… 69 MRI scans of the brains of people with OA have shown that people with OA have faster declines in hippocampal volume than people without OA and people with normal cognition, even after adjusting for factors such as age, gender, education, and APOE4 genotype. 70 Brain structural studies of people with depression have consistently found smaller hippocampal volumes in people with MDD compared to people without depression. 70 It is clear that there is an association between the functional and structural changes in the specific brain regions involved in OA pain processing and depressive symptoms.…”
Section: Potential Mechanisms Of Oa and Comorbid Depressionmentioning
confidence: 99%
“… 70 Brain structural studies of people with depression have consistently found smaller hippocampal volumes in people with MDD compared to people without depression. 70 It is clear that there is an association between the functional and structural changes in the specific brain regions involved in OA pain processing and depressive symptoms. In fact, few studies exist for the depression comorbid OA group, which makes it difficult to compare more clearly the changes in the brain of patients with OA and comorbid depression.…”
Section: Potential Mechanisms Of Oa and Comorbid Depressionmentioning
confidence: 99%
“…According to Xue, in 2018, the prevalence of dementia in an OA group was higher than that in the non-OA group (HR 1.42, 95% CI, 1.30-1.54); OA treatment reduced the risk of dementia [3]. Despite ongoing epidemiological studies on the correlation between dementia and OA [4][5][6], there is still no direct evidence showing its causal relationship.…”
Section: Introductionmentioning
confidence: 99%